Structure and functional characterization of the atypical human kinase haspin. - Eswaran, J; Patnaik, D; Filippakopoulos, P; Wang, F; Stein, R; Murray, J; Higgins, J; Knapp, S (2009)
The protein kinase haspin/Gsg2 plays an important role in mitosis, where it specifically phosphorylates Thr-3 in histone H3 (H3T3). Its protein sequence is only weakly homologous to other protein kinases and lacks the highly conserved motifs normally required for kinase activity. Here we report structures of human haspin in complex with ATP and the inhibitor iodotubercidin. These structures reveal a constitutively active kinase conformation, stabilized by haspin-specific inserts. Haspin also has a highly atypical activation segment well adapted for specific recognition of the basic histone tail. Despite the lack of a DFG motif, ATP binding to haspin is similar to that in classical kinases; however, the ATP gamma-phosphate forms hydrogen bonds with the conserved catalytic loop residues Asp-649 and His-651, and a His651Ala haspin mutant is inactive, suggesting a direct role for the catalytic loop in ATP recognition. Enzyme kinetic data show that haspin phosphorylates substrate peptides through a rapid equilibrium random mechanism. A detailed analysis of histone modifications in the neighborhood of H3T3 reveals that increasing methylation at Lys-4 (H3K4) strongly decreases substrate recognition, suggesting a key role of H3K4 methylation in the regulation of haspin activity.